Manajemen Kurikulum Di Sekolah Dasar Negeri Sumbersari Kecamatan Parigi Selatan Kabupaten Parigi Moutong - Junetri, Jesiyani; Susanti, Ani; Salingkat, Syarif Permana (JPS: Journal of Publicness Studies, 2026)
This study aims to determine and analyze how Curriculum Management is implemented at Sumbersari Public Elementary School, Parigi Selatan District, Parigi Moutong Regency. Using the theoretical approach of Stephen P. Robbins and Mary Coulter which includes aspects of planning, organizing, leadership, and supervision. The research method is qualitative with observation, interview, and documentation techniques, as well as data analysis of the Miles, Huberman, and Saldana models. The results of the study indicate that Curriculum Management at Sumbersari Public Elementary School is not yet fully optimal, there are still certain obstacles in it. From the planning aspect, there are still obstacles in teachers' understanding of dynamic curriculum program changes so that further training is needed. The organizational aspect, the division of teacher tasks has been carried out well but the main obstacle lies in physical resources, limited physical facilities and infrastructure, such as a limited number of projectors (infocus), damaged toilets, the need for library and canteen rehabilitation and the unavailability of a UKS room. The leadership aspect, the Principal has carried out a leadership role through providing motivation, supporting the adaptation of the independent curriculum, and strengthening collaboration between teachers, students, and parents. Supervision aspects are carried out periodically by the principal and supervisory supervisors through routine evaluations and the implementation of Computer-Based National Assessments (ANBK) to monitor the quality of learning, but supervision of the school environment still needs to be improved in terms of security, namely the need for security guards or school guards.